Meta-Analysis: The Influence of Teaching Material to Improve 21st Century Skills in Physics Lessons - Vivi Mardian; Asrizal Asrizal (Berkala Ilmiah Pendidikan Fisika, 2021)
The rapid progress of science and technology is marked by easy access to education quickly. Skills that are needed today are often called 21st-century skills. 21st-century skills have become a necessity for students to continue their careers in the future. Physics is one of the lessons that are very close to nature. This research aims to show the influence of the use of physics teaching materials on the 21st-century skills of students is seen from the level of education, learning materials, and student learning outcomes. This research is a literature study of 16 articles on the description of Effect Size in educational studies. Overall, the effect size of the use of teaching materials on physics learning is 3.7. Based on the data analysis, it can be concluded that there is a strong influence in the use of physics teaching materials on the 21st-century skills of students seen from the level of education, learning materials, and student learning outcomes.